Study on the microstructure and properties of Fe-C-Si and Fe-C-Al Cast irons - Shaha, Sugrib Kumar; Haque, Md. Mohafizul; Khan, Ahsan Ali (Trans Tech Publications, Switzerland, 2011)
Two types of cast irons with Fe-C-Si and Fe-C-Al. alloy systems were investigated in the present study. In order to modify the microstructure and properties of cast iron, Al was added to low silicon pig iron that is in Fe-C-Al (Sorel metal) alloy system. Its effect was then studied with comparing to normal Fe-C-Si alloy system. Both cast irons were produced in sand mould of suitable design to provide all information regarding the structure and properties. The microstructure was analyzed using optical microscope which showed the distribution of graphite flakes in pearlite or ferro-pearlite matrix. The size of the graphite flakes in Fe-C-Al system was smaller and more evenly distributed compared to the Fe-C-Si alloy system. The cast product was also characterized by using XRD. The maximum hardness of the Fe-C-Al alloy was measured as 110.2 HRB compared to 89.32 HRB of the conventional Fe-C-Si alloy system. The impact test results showed that Fe-C-Al cast iron has higher impact property than Fe-C-Si cast iron.